Pengembangan Industri Kecil Menengah Produk Olahan Tiram di Desa Tibang - Andriansyah Andriansyah; Didi Asmadi; Sarika Zuhri; Prima Denny Sentia; Medyan Riza; Hidayaturrahmi Hidayaturrahmi; Nissa Prasanti (Universitas Teuku Umar, 2021)
Tibang Village is a village located in a coastal area in the city of Banda Aceh. This village is famous for its natural potential that produces oyster shells. Based on observations, these oyster shells are processed into edible nuggets and oyster crackers. The problem in this village is the lack of understanding of the community on how to manage and create potential industry with processed oyster shell products. The purpose of this article is to study and design the supply chain network in the management of oyster processed products. Supply chain management is an approach taken to increase the competitiveness of a product. The results of the study were socialized to villagers to increase understanding of the importance of managing oyster shell processed products from upstream to downstream. The results obtained are that in the management of oyster shells processed products, it is necessary to have actors who play a role in collecting raw oysters from farmers before they are processed into nuggets and oyster crackers